2011
DOI: 10.1021/ac202410q
|View full text |Cite
|
Sign up to set email alerts
|

Quartz Crystal Impedance Response of Nonhomogenous Composite Electrodes in Contact with Liquids

Abstract: A new model of quartz-crystal impedance (QCI) of nonuniform layers composed of bumps of carbon particles (either porous or nonporous) and a polymeric binder layer has been proposed. The solid particles are modeled by semispherical and oblate semispheroid bumps embedded into the "sea" of a polymeric binder layer. On the basis of this model and elaborating on the principles of hydrodynamic spectroscopy of composite electrode materials, the geometric and porous structure parameters of nanoporous carbon and nonpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…calculated for the experiment related to Figure 3 was 9.39. Based on parallel studies of complex electrochemical processes by EQCM, [21][22][23] we can attribute such a discrepancy to viscoelastic effects that limit the simple applicability of the Sauerbrey equation 24 for these measurements. All our tests with MgTFSI 2 /MgCl 2 solutions showed that during prolonged electrochemical measurements, an un-identified by-product was formed (and at least part of it precipitated on the electrode surface), a by-product which is associated with the passage of faradaic currents.…”
Section: Resultsmentioning
confidence: 99%
“…calculated for the experiment related to Figure 3 was 9.39. Based on parallel studies of complex electrochemical processes by EQCM, [21][22][23] we can attribute such a discrepancy to viscoelastic effects that limit the simple applicability of the Sauerbrey equation 24 for these measurements. All our tests with MgTFSI 2 /MgCl 2 solutions showed that during prolonged electrochemical measurements, an un-identified by-product was formed (and at least part of it precipitated on the electrode surface), a by-product which is associated with the passage of faradaic currents.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, due to clamping of the electrode particles, the mechanical deformation of the entire composite electrode layer becomes essentially non-uniform. [ 9 ] The description of the complicated solid-liquid interactions originating from variations in the effective electrode layer thickness, h , and its permeability length, ξ , upon ion insertion/ extraction is part of the hydrodynamic admittance problem [ 11,12 ] and is dealt with herein. Figure 2 summarizes the basic electroanalytical features of thin composite Ti 3 C 2 T x electrode coatings (active mass ≈ 60 µg cm -2 ) on a QC surface.…”
Section: Morphology and Electroanalytical Features Of 2d Ti 3 C 2 T Xmentioning
confidence: 99%
“…[10] Less known is that any QCM instrument recording both shifts in resonance frequency(F)and resonance width (W,ordissipation factor D = W/F)can be employed as asensitive probe of the potential-induced deformations of composite electrode coatings. [7,8,11] Thee lectrode particles deformations (i.e., achange in their shape and size) modify their hydrodynamic interactions with the contacting liquid, thereby directly affecting experimentally measured values of shifts in F and W. [7,8,11] In contrast to conventional mechanical measurements, [12] deformation of the polymeric binders in composite electrodes is caused by contracting/expanding intercalation particles rather than by applied external force.Y et, non-uniform binder distribution at the particle surface affects the character of the particles deformation. Thed eformation depends on the polymer and the solution nature (e.g., through the polymers elastic modulus), and is also af unction of the electrodes charging rates since the polymers elastic moduli are time (frequency)-dependent through av ariety of relaxation mechanisms.…”
mentioning
confidence: 99%
“…[14] Gel formation is further enhanced when at hin layer of NaCMC is strongly held by the intercalation particles after complete drying of the electrode at elevated temperature.S welling of the elastomeric network in aqueous solution facilitates aq uasi-uniform deformation of LiFePO 4 particles:the effective thickness of the porous electrodes layer decreases because the intercalation particles contract during Li-ions extraction, ensuring ad ecrease in DW due to reduction of solid-liquid hydrodynamic interactions. [7,11] In contrast, NaCMC remains completely rigid in aprotic solutions. [2] Figure 3C directly confirms this conclusion:the non-uniform deformation of the electrode'sa ctive mass (resulting in the increase of the dissipation factor) arises as ac onsequence of the non-uniform distribution of the rigid polymeric binder.…”
mentioning
confidence: 99%